Preliminary study of the genetic structure of domestic, peridomestic and sylvatic populations of Triatoma dimidiata (Hemiptera: Reduviidae) - JARAMILLO, CARLOS; RAMÍREZ-H., CAROLINA; DELGADO, PILAR; PINTO, NÉSTOR; AGUILERA, GERMÁN; GUHL, FELIPE (Revista Colombiana de Entomología, 2003)
In order to study the genetic structure of sylvatic, peridomestic and domestic populations of Triatoma dimidiata, we used the randomly amplified polymorphic DNA (RAPO) technique. The genetic flow among populations was estimated to determine the epidemiological risk of nondomiciliated populations in the transmission of Chagas disease. Fourteen sylvatic, 10 peridomestic and 15 domestic insects were analyzed. The estimated Wright "s Fst was 0.071 showing low genetic differentiation and an effective migration rate Nm of 3.3 suggesting a movement of at least three individuals per generation. These findings suggest that nondomiciliated populations of T. dimidiata represent an epidemiological menace for the transmission of Chagas disease, due to their ability to colonize dwelling. lt is necessary to perform: an epidemiological surveillance not only of the domestic populations but also on the peridomestic ones. lt is also important to carry out new and better control alternatives for reservoirs, and to offer a permanent education program to people at risk of infection.